Transmisión del tomato Venezuela virus por Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), en Maracaibo, Venezuela - Romay,Gustavo (2010)
The biological transmission of Tomato Venezuela virus (ToVEV) by biotype B of the whitefly species Bemisia tabaci (Gennadius) increased (21.7-95.0%), and the time for symptom expression decreased (16-12.6 days) as the number of viruliferous whiteflies allowed access for inoculation to susceptible tomato plants increased from 1 to 20 adults/plant. When acquired only as a nymph, adults of this biotype transmitted the virus to 88.3% of susceptible tomato plants, using 15 viruliferous individuals per test plant, corroborating the circulative nature of the transmission. Disease incidence further increased (up to 100%) when the individuals were allowed to feed again on a virusinfected plant as adults. Leaf area, plant height and dry matter were significantly affected in ToVEV infected tomato plants.